Peningkatan Kapasitas Pelaku Mikro Usaha Kecil Menengah (UMKM) di Desa Anggrawati melalui Kegiatan Pendampingan - Amelia Paramitha Mahanani; Irna Noerrochmah; Salahuddin El Ayubbi (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Micro, Small and Medium Enterprises (MSMEs) are businesses that have an important role in driving the wheels of the national economy. Anggrawati Village is an example of a village that moves its economic conditions by forming MSMEs. But unfortunately, several UMKM Anggrawati villages often have difficulty determining market segmentation and attracting consumers to be able to buy their products. These things are caused by inadequate promotion carried out and there are no distinctive features possessed by an SME. The aim of the MSME mentoring program is to assist MSME entrepreneurs in finding additional capital alternatives, to help in designing business labels, and to help expand the area of marketing both offline and online. The method used is a visit, problem identification, practice, and decide on a solution together. The result of the assistance was that MSMEs showed enthusiasm during the activities. The SMEs have succeeded in planning the logo and label for rebranding but have not yet been willing to change the logo in the future, the UMKM has successfully registered its products in one of the Indonesian market places, and the SMEs also learned the things needed in making a proposal for funding. Keywords: marketing, mentoring, MSME, rebranding